Impact of Foreign Direct Investment on Economic Growth: Comparative Analysis in Ecuador, Peru and Colombia 1996-2016 - Freddy R. Camacho; Yanina S. BajaÃ±a (International Journal of Economics and Financial Issues, 2020)
The present investigation has the purpose of evaluating whether there is a Granger causality relationship in the 1996-2016 historical trajectory between the study variables, Foreign Direct Investment (FDI) and economic growth of Ecuador, with its commercial partners Colombia and Peru; considering the importance that its implications could contribute to political-economic decisions. The analysis was performed taking data from Ecuador, Peru and Colombia with a temporal sample in the period 1996-2016 on a quarterly basis applying autoregressive vectors to determine the relationship between the mentioned variables. The results indicate that GDP does not cause FDI in any of the countries analyzed. However, in Ecuador and Peru FDI has a significant Granger-causality effect on GDP. A possible explanation for this last result may be that FDI has a non-linear effect on production. Both Ecuador and Peru have a low level of FDI over GDP in relation to Colombia.